(3TQM bUjOI GdHQOI ddHhUjQis - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3eMeO Hf SYjO Hf MeGO GdUfgGLj GdHhUjQj, (B696 (3g`,J (B696 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg eSJMb GdJeLjO ajbhd NGdO Hf YHO Gddg GdCRgQi (B: (3bO SCdJfi CjgG GdCN GdfLjM Cf CVY TQMkG dWjakG HQOg GdedjM s
(3BNQgG (B:s
(3jGef gh GdQH GddWja HYHGOg CSCdc Ydi SjOi eMeO GdPi LeYJ ajg GdecGQe hGdNjQGJ GfJgi HMeO Gddg s
(3GdTQM GdeaUd SeGg GdRHOI ai TQM bUjOI GdHQOI hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - - (3U (B165 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1332s
Keywords: (3GdCOHs